Women participation in politics a study of public perception in the northern part, Malaysia - Halim, Nurulhazany; Zainuddin, Ruslan (2016)
Several women are disadvantaged in the four northern state of Malaysia based on gender and associated challenges; nevertheless, a majority of these women desired to fight for positions in respective of their educational background for empowerment.The aim of this study will be to examine people’s perception on women participation in politics.Qualitative research design will be adopted for the study.Data will be collected with the Interview Schedule for public and members of the major political parties in the region 20 participants which comprises both male and female in the four state.The purposive sampling is to select cases rich with information that will enhance the questions being studied.The focus of the data collection will be on the challenges of women participation in politics.The purpose of this study was to examine issues that prevent women from participate or aspire to get to elected positions in the states under this study.In addition, data was collected and analyzed using inductive coding procedures to categorize the general’ challenges of women participation in political processes. The implication of this study is to contribute to political, social, family, and governing process to change the general public opinion on the women participation in politics by informing parties and government administrators on the enabling environments for the women to realise their dreams and aspirations in life.